x^2-3x-1=0 by using quadratic formula
Answers
Answered by
0
Answer:
7iju
Step-by-step explanation:
//98i69797
Answered by
0
Answer:
Use the quadratic formula
=−±2−4√2
x=\frac{-{\color{#e8710a}{b}} \pm \sqrt{{\color{#e8710a}{b}}^{2}-4{\color{#c92786}{a}}{\color{#129eaf}{c}}}}{2{\color{#c92786}{a}}}x=2a−b±b2−4ac
Once in standard form, identify a, b and c from the original equation and plug them into the quadratic formula.
2−3−1=0
x^{2}-3x-1=0x2−3x−1=0
=1
a={\color{#c92786}{1}}a=1
=−3
b={\color{#e8710a}{-3}}b=−3
=−1
c={\color{#129eaf}{-1}}c=−1
=−(−3)±(−3)2−4⋅1(−1)√2⋅1
x=\frac{-({\color{#e8710a}{-3}}) \pm \sqrt{({\color{#e8710a}{-3}})^{2}-4 \cdot {\color{#c92786}{1}}({\color{#129eaf}{-1}})}}{2 \cdot {\color{#c92786}{1}}}x=2⋅1−(−3)±(−3)2−4⋅1(−1)
2
mark as brainleist
Similar questions